How can South-South cooperation contribute to a knowledge-based development strategy - Thomas, Clive (2000)
Questions what countries of the South can do to implant knowledge building as the driving force for constant innovation and successful competition in the global context. Discusses and weighs some needed practical strategies and support policies.